Investigation of the properties of different potato varieties and analysis of the starch structure - Katalin Bodor; Borbála Tamási; Adél Len; Ágnes Keresztesi; Róbert Szép; Zsolt Bodor (Applied Food Research)
Potatoes (Solanum tuberosum) are widely cultivated in the Ciuc Basin, where favorable soil conditions and specific climate favor potato cultivation. This study examines six potato cultivars (Red Lady, Bellarosa, Captiva, Arizona, Esmee and Santé), and analyzes key parameters such as dry matter content, moisture content, tuber count per nest, nest weight and starch structural properties. It also considers meteorological factors including temperature, humidity and precipitation. The results revealed significant varietal differences, with Santé exhibiting the highest dry matter content (22.86 %), making it a promising candidate for applications requiring higher starch density. In contrast, Arizona had the lowest dry matter content (17.76 %), indicating potential for improvement through breeding. The average nest weight prior to harvest was 1.74 kg, Bellarosa produced an average of 9 tubers per nest, Esmee 11, and the remaining cultivars averaged 12 tubers per nest.Microstructural analysis of starch using scanning electron microscopy (SEM) and small-angle neutron scattering (SANS) revealed cultivar-specific variations in the crystalline and amorphous regions of starch granules over time. The lamellar architecture of the semicrystalline growth rings remained stable in hydrated samples. Analyzing the correlations between environmental factors and tuber characteristics, the findings underscore the importance of cultivar-specific cultivation strategies to optimize yield and starch quality. These findings are particularly relevant for breeders, growers, and stakeholders in the potato industry.